ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN CV. SAKILA BANYUWANGI - Helmi Agus Salim; Ahmad Sauqi (MBA - Journal of Management and Business Aplication, 2023)
The business world cannot be separated from competition, where service quality is one of thefactors that must be owned by every business unit if you want to survive in business orbusiness competition. So that customers are satisfied with the services provided. The purposeof this study was to determine the effect of service quality on customer satisfaction eitherjointly or partially on CV. Sakila Banyuwangi. CV. Sakila is a business in the field ofprinting, digital printing and screen printing whose business units include the manufacture ofprint media and advertising. The type of research used in this research is descriptive researchthat uses a quantitative approach. The analysis technique used is descriptive analysistechnique and by using multiple regression. While the sample technique used is a non-probability sample that uses a total sample of 100 people. This study uses primary datasourced from direct observation and questionnaires distributed to respondents, where therespondents are customers of CV. Sakila Banyuwangi which is then analyzed using multiplelinear analysis. Based on the results of this study, service quality (X) which consists ofphysical evidence, reliability, responsiveness, assurance and empathy simultaneously has asignificant effect on customer satisfaction with a value (p value) of 0.003 < 0.05. Some of theresults of the t-test that tested the variable (x) against (y) partially showed that only theempathy variable did not have a significant effect on customer satisfaction with a totalsignificance (X5 value) of 0.353 <0.05. The implication of the results of the research aboveshows that the variables of Physical Evidence, Reliability, Responsiveness, Assurance have asignificant effect on managerial performance, this is what makes CV. Sakila Banyuwangiprinting is stable and can run smoothly in running its business in the world of printingservices, although in this study there is one variable, that is Empathy has no significantpositive effect.